(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Meningiomas are the most common intracranial tumors and frequently observed in older adults with a high prevalence in females. This report presents the case of a 71-year-old woman with known diabetes mellitus, hypertension, ischemic heart disease and history of tuberculosis, who was under evaluation for mildly raised parathyroid hormone level. She was eventually referred for a 99m Tc- Sestamibi SPECT parathyroid scan—in which a meningioma was incidentally detected. Bangladesh J. Nuclear Med. 28(2): 364-367, July 2025